Transportation of Children In Ground Ambulances: Professionals' Knowledge and Safety Measures. - Lomba, Maria de Lurdes Lopes de Freitas (2016)
Summary The transport of children in ground ambulances is a rarely studied topic worldwide. The ambulance vehicle is a unique environment with particular challenges for the safe, correct and effective transportation of patients. Unlike the well developed and available guidelines on the transportation of children in motor vehicles, there is a lack on specifications for transporting children in ambulances. Nurses are called daily to transfer children to hospitals or other care centres, so safe transport practices should be a major concern. Methods An exploratory - descriptive study and quantitative analysis was conducted. The safety measures used by the professionals in the transportation of children in ambulances were analysed based on the NHTSA (National Highway Traffic Safety Administration) recommendations. A questionnaire was applied to 135 nurses and firefighters/crew of Portuguese ambulances using 4 possible transport situations and covering 5 paediatric age groups. Results There are a variety of safety measures used by professionals and a significant difference between actual mode of transportation and the mode they consider to be the ideal. In addition, findings showed that scores related to what ambulance crews do in these scenarios reflect most satisfactory levels of transportation rather than the optimum levels, according to NHTSA recommendations. Variables as gender, educational qualifications, occupational group and local where professionals work seem to influence the transport options. Female professionals and pediatric nurses do a safer transportation of children in ambulances than other professionals. Conclusion The results suggest the need for investment in professional training and further regulation for this type of transportation.